Whose Face? Us and them in English – Polish Consecutive Interpreting - Warchał, Krystyna; łyda, Andrzej; Jackiewicz, Alina (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
The authors are interested in a situation where concern for the face of the receiver and/or the identity and group membership of the interpreter can become factors that influence the process of interpreting. The aim of this paper is to look into the performance of advanced trainee interpreters in consecutive interpreting tasks that involve open criticism or direct praise of the target audience. More specifically, the authors are concerned with the type and extent of face-work carried out in tasks involving face-threatening acts and with the possible correlation between the interpreter’s performance in such tasks, the choices made by the interpreter and his or her relationship with the group of ultimate receivers.